After all we are only human: leading people in organizational change - Karp, Tom (Henry Stewart Talks, 2009)
The case for change, Top down, management science, direction and control theories, Human resources and organizational development theories, Organizational learning theories, Living theories, spiritual, ideological theories, Important premises of change management, Common approaches to change management and everyday reality, The organization, People and expression of identity in organizations, Macro and micro perspectives on change, Cognitive, emotional and behavioral challenges, The organizational iceberg, What can leaders of change do?